PERFORMATIVITY IN PROTESTS IN THE EXAMPLE OF ACTIVIST GROUPS IN MACEDONIA - Sonja Zdravkova Djeparoska (ICTM NC Macedonia, 2020)
The analysis of music and dance in a society cannot neglect social conditions, political processes, or social context. Over the past few years, several major political changes took place in Macedonia, fol- lowed by mass demonstrations, protests and civic activities. The block of civic organizations, activists, students, university professors and cit- izens who demanded changes in the functioning and governance of the state were organized in several movements known as the Student and Professor Plenum, the Colorful Revolution, etc. Apart from expressing their views in the streets, they organized a series of activities that used music, dance and performance as tools. This paper is devoted to the analysis and interpretation of these performances which in this case have received an activist, social engagement role. The theater, which plays a role in the social awakening of the population in order to en- courage critical attitudes, is not a novelty. This type of performance is predominantly related to the work of directors Bertolt Brecht, Erwin Piscator, and Antonin Artaud. The activities that took place in the Mac- edonian capital, Skopje, may not have been directly mirroring the mod- els of this kind of performance, but to a large extent caused an identical effect that was part of the goals of this kind of performance and theatri- cal aesthetics. From a range of very diverse outdoor performances, this paper will focus on the most striking ones. The analysis will be con- nected with several layers and will make a comparison of the musical basis used as part of the protests, dance, and performances that were presented. These performances produced completely different mean- ings and sent messages that are not present in a usual performance con- text. Music and dance suddenly became tools in a tumultuous, transi- tional moment in contemporary Macedonian history in which perfor- mance gained a new meaning, interpretation and task.
Keywords: Macedonia, protests, performance, music, dance